THE IMPORTANCE OF INTEGRATING MATHEMATICAL LITERACY IN THE PRIMARY EDUCATION CURRICULUM: A LITERATURE REVIEW - Joni Wilson Sitopu; Majidah Khairani; Melia Roza; Loso Judijanto; Aslan (International Journal of Teaching and Learning, 2023)
This comprehensive literature review investigates the critical importance of integrating mathematical literacy into the primary education curriculum. Mathematical literacy, a holistic concept that involves the complete understanding, practical application, and thoughtful analysis of mathematical information across diverse contexts, is a transformative force in molding the foundational skills of young learners. This review extensively explores the myriad benefits arising from the intentional inclusion of mathematical literacy, emphasizing its pivotal role in fostering logical thinking, aligning with the demands of 21st-century skills, and augmenting global competitiveness among learners. Despite acknowledged challenges in implementation, the long-term advantages for individual students and society are resoundingly underscored, positioning mathematical literacy not only as a pedagogical necessity but as a strategic investment in the future of education and national progress. Furthermore, this literature review goes beyond surveying existing research and academic journals; it represents a nuanced synthesis of diverse perspectives and findings. Drawing insights from pertinent publications delves into the practical implications and real- world applications of integrating mathematical literacy. The review is valuable for educators, policymakers, and curriculum developers, offering actionable insights to inform decision-making processes. Through meticulously examining the literature, this review advocates for acknowledging mathematical literacy and its intentional and meaningful incorporation into primary education curricula. It contributes substantively to ongoing conversations in the educational landscape, promoting a paradigm shift towards a more holistic and impactful approach to mathematical education.